Talk in online video games: study of how the use of jargon, social interaction, and representation in Overwatch affects the ability of women to immerse themselves in these spaces - Stander, Emily (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies)
This thesis investigates the impact on women of aggressive, demeaning and blaming talk in the online video game* space. The objective is to understand how players talk to each other and how this kind of talk presents issues for women trying to enter the online gaming sphere and become recognised as players. The main method was participatory observation and interviews with women who have experienced such talk. Key results which came from this research is that the process of keeping specific people out of communities through different means of talk - gatekeeping, women being viewed as objects of sexual gratification for men through bad representation in video games and media and using women as scapegoats for frustration and blame in the competitive online video game space, are the main issues which arise from the way players communicate with each other. In conclusion, the research presented that there needs to be an effective system of unlearning and relearning these behaviours in communities and a change in the way women are represented and seen in media is necessary in order to change the behavioural patterns which exist in gaming culture.
Keywords: Internet games -- Social aspects; Video gamers -- Language; Women video gamers; Cyberbullying; Online hate speech; Online trolling; Online chat groups; Women -- Social conditions; Women -- Sociological aspects; Overwatch (Video game); Internet games -- Sex differences; Sex discrimination against women